Volume 5: 25th International Conference on Design Theory and Methodology; ASME 2013 Power Transmission and Gearing Conference 2013
DOI: 10.1115/detc2013-13072
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Prototyping Strategies in Conceptual Phases of Design: Framework and Experimental Assessment

Abstract: Prototyping may be simultaneously one of the most important and least formally explored areas of design. Over the last few decades, designers and researchers have developed many methodologies for ideation, product architecture, design selection, and many other aspects of the design process. However, there have been relatively few methodologies published regarding the efficient and effective development of prototypes for new products. This research explores a methodology for enhancing the prototyping process. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 25 publications
(12 reference statements)
0
45
0
2
Order By: Relevance
“…Prototyping represents a large sunk cost for most companies that is overcome through the launch of a successful product; however, estimates indicate that 40-50% of product development costs are spent on failed products or products that do not yield adequate return 14,37 . Previous research has shown that breakthroughs and innovations made by engineering designers are dependent upon the ability to experiment and test 12 .…”
Section: Prototyping Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Prototyping represents a large sunk cost for most companies that is overcome through the launch of a successful product; however, estimates indicate that 40-50% of product development costs are spent on failed products or products that do not yield adequate return 14,37 . Previous research has shown that breakthroughs and innovations made by engineering designers are dependent upon the ability to experiment and test 12 .…”
Section: Prototyping Literaturementioning
confidence: 99%
“…In order to understand prototyping at a deeper level and highlight the gaps in the prototyping literature, 46 papers were critically reviewed. We build upon Christie, et al 37 and Camburn, et al's work 14 by adding literature from engineering education 2,5,6,22,[38][39][40] , human computer interaction 9,27,34,41 , industrial design [44][45][46][47][48][49] , and design thinking studies 7,[50][51][52][53] . In the following section we use this literature to derive definitions for each of our prototyping lenses.…”
Section: Prototyping Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Prototyping of ideas, at least virtually as part of a simulation, or physically as a concept or functional model 8. Relatively low-cost materials for creating prototypes 21,22,23,24 9. Implementing technology, such as layer-based manufacturing/rapid prototyping equipment, for quickly transforming ideas into reality, 25, 26 and 10.…”
Section: Related Researchmentioning
confidence: 99%